2005
DOI: 10.1111/j.1365-2591.2005.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper–zinc superoxide dismutase activity in healthy and inflamed human dental pulp

Abstract: These results demonstrate a potential role for Cu, Zn-SOD during dental pulp inflammation in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
0
15
1
1
Order By: Relevance
“…SOD is a detoxifying antioxidant enzyme which acts against free radicals by catalyzing the dismutation of the superoxide ion into oxygen and hydrogen peroxide [Halliwell, 1999;Varvara et al, 2005]. This study showed an increase in SOD activity in saliva in caries-active adults when compared with that of caries-free individuals, suggesting its role as an antioxidant.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…SOD is a detoxifying antioxidant enzyme which acts against free radicals by catalyzing the dismutation of the superoxide ion into oxygen and hydrogen peroxide [Halliwell, 1999;Varvara et al, 2005]. This study showed an increase in SOD activity in saliva in caries-active adults when compared with that of caries-free individuals, suggesting its role as an antioxidant.…”
Section: Discussionmentioning
confidence: 56%
“…The estimation of SOD enzyme activity was carried out by the Beauchamp and Fridovich method [Green, 1970;Beauchamp and Fridovich, 1971;Gråhn et al, 1988;Varvara et al, 2005]. The substrate used for the assay consisted of nitro blue tetrazolium chloride, which reacts with superoxide anions produced upon illumination of riboflavin in the presence of methionine as an electron donor to produce formazan, which is a blue-colored complex.…”
Section: Estimation Of Sod Activity By Nitro Blue Tetrazolium Chloridmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, different pH conditions were used in different studies of SOD enzyme activity, which can also explain the discrepancy found in enzyme activity and consequently the results of the studies (Davis et al. 1991, Marklund 1992, Varvara et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports showing an increase in SOD in cases of irreversible pulpitis (Bodor et al. 2007) and reduction in its activity in irreversible symptomatic pulpitis tissue (Varvara et al. 2005).…”
Section: Discussionmentioning
confidence: 99%